2009
DOI: 10.1017/s002211200900634x
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of the inflectional instability of a laminar separation bubble

Abstract: This is an experimental and theoretical study of a laminar separation bubble and the associated linear stability mechanisms. Experiments were performed over a flat plate kept in a wind tunnel, with an imposed pressure gradient typical of an aerofoil that would involve a laminar separation bubble. The separation bubble was characterized by measurement of surface-pressure distribution and streamwise velocity using hot-wire anemometry. Single component hot-wire anemometry was also used for a detailed study of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
114
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(135 citation statements)
references
References 34 publications
20
114
1
Order By: Relevance
“…These and other works on boundary layers with separation bubbles thus indicate, the dominant peaks of the disturbances are located at the critical layer, these peaks increase with distance from the separation point and achieve maximum values which can be attributed to the critical layer. Häggmark et al (2000) experimentally studied a 2-D separation bubble on a flat plate by means of hot-wire anemometry and found that the streamwise velocity disturbances for both natural and forced cases exhibited three maxima; Diwan & Ramesh (2009) experimental results confirmed this observation.…”
Section: Modification Of the Linear Instability Modesmentioning
confidence: 78%
See 1 more Smart Citation
“…These and other works on boundary layers with separation bubbles thus indicate, the dominant peaks of the disturbances are located at the critical layer, these peaks increase with distance from the separation point and achieve maximum values which can be attributed to the critical layer. Häggmark et al (2000) experimentally studied a 2-D separation bubble on a flat plate by means of hot-wire anemometry and found that the streamwise velocity disturbances for both natural and forced cases exhibited three maxima; Diwan & Ramesh (2009) experimental results confirmed this observation.…”
Section: Modification Of the Linear Instability Modesmentioning
confidence: 78%
“…The more recent research demonstrated that the primary instability mechanism in a separation bubble is inflectional in nature (Diwan & Ramesh 2009). In figure 12, normalised streamwise components of the base flow and the perturbation in the symmetric plane for λ = 81 mm are shown.…”
Section: Destabilisation Mechanismmentioning
confidence: 99%
“…Gaster & Grant (1975) were the first to introduce an impulsive disturbance, exciting the full spectrum of instability modes, thus generating a wave packet through selective amplification. This method was subsequently used by Watmuff (1999) and Diwan & Ramesh (2009). It must be noted that impulsive disturbances have, so far, been locally introduced at a single point, usually a pressure tap.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that disturbances developing in a LSB are initially convectively amplified via a Kelvin-Helmholtz instability mechanism, similar to free shear layers (Ho & Huerre 1984;Watmuff 1999;Marxen et al 2015). Inviscid inflectional and Göertler type instability mechanisms have been proposed by Diwan & Ramesh (2009) and Marxen et al (2009) respectively. Furthermore, Theofilis et al (2000) conjectured a self-exciting, globally unstable process in a disturbancefree numerical environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation